The Metamorphic Rocks-Hosted Gold Mineralization At Rumbia Mountains Prospect Area In The Southeastern Arm of Sulawesi Island, Indonesia - Hasria Hasria; Arifudin Idrus; I Wayan Warmada (UIR PRESS, 2017)
Recently, in Indonesia gold exploration activities are not only focused along volcanic-magmatic belts, but also starting to shift along metamorphic and sedimentary terrains. The study area is located in Rumbia mountains, Bombana Regency, Southeast Sulawesi Province. This paper is aimed to describe characteristics of alteration and ore mineralization associated with metamorphic rock-related gold deposits. The study area is found the placer and primary gold hosted by metamorphic rocks. The gold is evidently derived from gold-bearing quartz veins hosted by Pompangeo Metamorphic Complex (PMC). These quartz veins are currently recognized in metamorphic rocks at Rumbia Mountains. The quartz veins are mostly sheared/deformed, brecciated, irregular vein, segmented and relatively massive and crystalline texture with thickness from 1 cm to 15.7 cm. The wallrock are generally weakly altered. Hydrothermal alteration types include sericitization, argillic, inner propylitic, propylitic, carbonization and carbonatization. There some precious metal identified consist of native gold and ore mineralization including pyrite (FeS2), chalcopyrite (CuFeS2), hematite (Fe2O3), cinnabar (HgS), stibnite (Sb2S3) and goethite (FeHO2). The veins contain erratic gold in various grades from below detection limit <0.0002 ppm to 18.4 ppm. Based on those characteristics, it obviously indicates that the primary gold deposit present in the study area is of orogenic gold deposit type. The orogenic gold deposit is one of the new targets for exploration in Indonesia